Pergeseran Wacana Relasi Gender Dalam Kajian Tafsir Di Indonesia: (Perbandingan Penafsiran âAbd Al-Rauf Singkel Dan M. Quraish Shihab) - Saifuddin, Saifuddin (Muadalah, 2014)
This study tries to picture the shift in gender relations discourses in the interpretation paradigm in Indonesia by comparing the interpretation (tafsir) of âAbd al Rauf Singkel and M. Quraish Shihab. The result of study shows that there are some similarities and differentiations in the pattern of the compared interpretation of the two Indonesian Malay scholars on gender versus. âAbd al Rauf Singkelâs interpretation generally follows the traditional interpretation paradigm, yet the creativity elements still can be found. As the main source, The interpretation of Al-Mustafid which refers to al-Jalalain interpretation may describe the mindset of âAbd al Rauf Singkel whose his is in the traditional interpretation mainstream and which is gender bias. It is reflected in some of his interpretations. However, His views are more moderate and tolerant as shown in his interpretation on the issues of women creation and leadership. The shift of gender relation discourse is more visible in the interpretation of Quraish Shihab. He seems to have his own interpretation which does not fully follow the view of both traditional and contemporary interpretation. He, for example, interprets ânafswahidahâ as âAdamâ whose couple is Eve. However, he does not agree that Eve was created from Adam himself, but from Adamâs type. Thus, he is in a position between the traditional and the contemporary. A similar tendency can also be seen from other themes. These interpretations are a step further than the previous Indonesian commentators (mufasir), not least âAbd al Rauf Singkel.